Applications of Vesicular Arbuscular Mycorrhizal Fungi for Sustainable Agriculture in Jordan - Al-Momany, Ahmad Al-Raddad (Jordan Journal of Agricultural Sciences, 2021)
The beneficial vesicular-arbuscular mycorrhizal fungi are found in the rhizosphere of many plants. These fungi are promising for sustainable agriculture especially in poor soils and under stress conditions. Many genera were naturally found in Jordan soils, especially Glomus, and were significantly effective in improving plant growth of several vegetable crops whether they were growing under mineral deficiency or drought conditions. Also, many soil-borne fungi as Fusarium, Verticillium, and Rhizoctonia as well as root-knot nematodes were successfully controlled under Jordan’s conditions. This type of biological control has a lower cost impact, safe and environment friendly.